Changes of tissue factor and tissue factor pathway inhibitor in neonatal jaundice due to infection - Yue, Shao-jie (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2003)
OBJECTIVE: Tissue factor (TF) is an important factor in extrinsic coagulation. Tissue factor pathway inhibitor (TFPI) is a negative regulator of coagulation mediated by TF. Studies on TF and TFPI focus mainly on adult objects, seldom have been done on newborns, especially on sick newborns. The aim of this study was to observe the changes of TF and TFPI in plasma of newborns with infection jaundice and to research the effect of jaundice and infection on the balance of TF and TFPI in newborns